Is Objective Structured Practical Examination a Better Option than Conventional Practical Examination in Assessing Students’ Competency? An Analytical Research - Arup J. Rout; Pallabi Dasgupta; Tushar K. Saha; Daliya Biswas (Indian Journal of Community Medicine)
Background: There was always a need for some innovative assessment method like an objective structured practical examination (OSPE) which is objective, reliable, and valid over conventional practical examinations (CPEs), which lack objectivity and reliability and carries risk of teachers’ bias as learning is assessment-driven. The aim of this study was to find out the effectiveness of OSPE over CPE among seventh-semester medical students and to assess the objectivity of structured questions among different OSPE stations. Materials and Methods: A total of 207 students appeared in the seventh-semester examination in community medicine, and they were divided into three groups depending on their total marks. Each student had to face both OSPE stations and conventional viva voce tables and their scores were recorded. A paired T-test was done to assess differences in mean marks between OSPE and CPE. A one-way analysis of variance (ANOVA) was done to compare the OSPE station-wise mean among different series of examinations. Results: The high-scorer students secured significantly higher mean marks of 30.30 ± 3.94 in OSPE than in CPE (26.93 ± 3.85). The mean marks obtained by high-scorer students showed no significant difference except in one station. Among the low-scorer group, statistically significant differences in mean marks were found among various stations. Conclusions: OSPE is an effective tool of assessment than CPE. Still, meticulous care is to be taken in designing respective OSPEs, and proper training of assessors is also needed, to avoid biases.